Implementasi Peningkatan Kompetensi Siswa Melalui Muatan Lokal Primary Global Islamic School - Wijayanti, Octy; Fuad, Nurhattati; Rahmawati, Desi (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2024)
This research used qualitative approach with case study as their methodology. The instruments were used in this research are observation, interview, and documentation. This research was conducted in Primary Global Islamic School condet, East Jakarta. The observation, interview, and documentation conducted toward school teacher for grade III and IV. The aims of this research is to describe the design of local content such as English subject and Al- Qur’an education, and analyzing the implementation of the local content in appartein to increasing speaking ability in english for studentd. The local content is a part of four pilar academics in which the exellency from Primary Global Islamic Scool condet. Therefore, the students not only excel speaking in english but also able learn Al Qur’an so that the student is ready to be the leader of rahmatan lill alamin for the strong foundation to face the rapid change of the global world.